THE EFFECTIVENESS OF INTERVENTION DUJHA JERKY (SWEET POTATO LEAVES–CHICKEN LIVER) ON HEMOGLOBIN LEVELS OF PREGNANT WOMEN IN THE WORKING AREA OF SUKARAMI PUBLIC HEALTH CENTER, LAHAT - Kristina, Meilia; Nilawati, Nurul Salasa; Susyani, Susyani (Jurnal Gizi dan Pangan Soedirman, 2025)
Background: Anemia in pregnancy remains a significant public health concern including in the working area of Sukarami Public Health Center, Lahat Regency, where the prevalence reached 38.8% in 2024. Iron deficiency is the leading cause of this condition. One alternative effort to increase hemoglobin levels is by providing iron-rich functional foods such as DUJHA jerky (a combination of sweet potato leaves and chicken liver). Objective: to determine of effectiveness of DUJHA jerky consumption on hemoglobin levels among pregnant women. Methods: This study employed a pre-experimental design with a one- group pretest-posttest approach. a total of 32 pregnant women were selected through total sampling. The assessments included organoleptic testing, nutrient content analysis, hemoglobin level measurement, and evalution of macro and micronutrient intake before and after the intervention. Data were analyzed using a paired t-test. Results: DUJHA jerky formula 2 was most preferred by panelists. The nutritional content per 100 g includes: energy 512.9 kcal, protein 20.6 g, fat 34.69 g, carbohydrate 32.2 g, iron 14.1 mg, and vitamin C 0.8 mg. The average hemoglobin level increased from 10.1 g/dL to 10.7 g/dL post-intervention.Statistical analysis showed a significant difference (p=0.000), indicating effectiveness. Conclusion: DUJHA jerky is effective in increasing hemoglobin levels in pregnant women and has the potential to be developed as an alternative functional food to prevent anemia.